The Digital Literacy Instruments for University Students - Ismaul Fitroh; Disman; Kokom Komalasari; Mamat Ruhimat (Universitas Pendidikan Ganesha, 2023)
Nowadays in the digital era, obtaining information is a very easy task, however, critical thinking from many university students in reality are still lacking and they have a high plagiarism level. This problem can be solved if the students have a digital literacy ability. The purpose of this research is creating a digital literacy instrument for students. The method applied in this research was R&D (Research and Development) research method with RDR (Research, Development, and Research) model. Subject of this study were two (2) expert lecturers in their field and collaborated with 30 students as test subjects. The method of data collection was questionnaires and interview, whereas the data analysis technique applied in this research was qualitative analysis with product moment correlation technique. The result of this research showed the content validity from the digital literacy coefficient of the students was 1, 00 which interpreted as a very high validity value. While the result of reliability test calculation showed r11 value was 0.88 which means the instrument is reliable since reliability coefficient value obtained a number greater than 0.60. Therefore, it can be concluded the digital literacy instrument from this research can be used to evaluate the students’ digital literacy ability. The implication of digital literacy instrument usage hopefully can help students to improve the quality of their learning process.